Development of an immunochromatographic test strip for the rapid detection of aristolochic acid A in herbal medicinal materials. Issue 3 (21st November 2021) - Chen, Xianrui; Huang, Ting; Huang, Zhibing; Han, Quanbin
Abstract: Introduction: Plants containing aristolochic acid and its derivatives are nephrotoxic, mutagenic, and carcinogenic to humans; chronic diet poisoning caused by the aristolochic acid is the cause of endemic (Balkan) nephropathy and related cancers. Objective: To develop a colloidal gold immunochromatographic test strip (ICS) based on the competitive format for the rapid detection of aristolochic acid A (AA‐A) in herbal medicinal materials. Materials and methods: For the ICS based on gold nanoparticles (AuNPs), the antigen [AA‐A–bovine serum albumin (BSA)], and goat anti‐mouse IgG were drawn on the nitrocellulose membrane as the test line (T line) and the control line (C line), respectively. Monoclonal antibody (MAb)–AuNP conjugates were sprayed onto the conjugate pad. The sensitivity of the ICS was 6 ng/mL, and the test was completed in 10 min. The analysis of AA‐A in traditional Chinese medicine samples showed that the ICS results were in good agreement with those obtained by high‐performance liquid chromatography methods. Conclusion: These results demonstrated that the ICS test could be used as a reliable, rapid, cost‐effective, and convenient qualitative tool for on‐site screening techniques to detect AA‐A in herbal medicinal materials without any special instrumentation. Abstract : An immunochromatographic strip (ICS) test for aristolochic acid was developed, and the ICS of aristolochic acid showed sensitivity of 6.0 ng/mL. The ICS is a rapid, cost‐effective, for on‐site screening technique for AA, and could detect aristolochic acid (AA) in herbal medicinal materials and food.